IMPLEMETASI KEBIJAKAN TENTANG PENCEGAHAN DAN PEMBERANTASAN PERDAGANGAN ORANG DI KOTA PONTIANAK - Anneke Cynthia Pelealu E01109042 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article raised the issue about implementation of local regulations number 07 2007 about prevention and eradication of human trafficking at Pontianak city especially at managing unit of rehabilitation and reintegration social and labor department of Pontianak. Aims of the implementation policy programme of preventing and eradiction of human trafficking are early prevention for the victim with conducting prevention, services, rehabilitation and social reintegration. It also aims to protect rights of life of citizens by state. Social department of Pontianak especially section unit of social welfare is a strategic media for handling human trafficking victims in order to protect and rehabilitation them at Pontianak. Human resources in socil welfare unit of Sosial Departement in order to handle the human trafficking are still limited thus it impact to not maximum service to victims. Communication conducted by unit social welfare service of Social Departement in coordinating victim prevention programme with related institutions still weak in implement rehabilitation and reintegration social of human trafficking.Meanwhile, special skill still needed and could be received through some trainings and real social programme and more important is honest and socially minded. Condition of social, economic and politic environments of Pontianak almost similar with other area at Kalimantan Barat in which susceptible to human trafficking, however politic condition at Pontianak are relative stable or in good condition, so it not impact to implementing rehabilitation and reintegration social programme to human trafficking at Pontianak. Key Words: Implementation, Policy, Preventing and Human Trafficking